Role of Extracellular Vesicles in Amyotrophic Lateral Sclerosis - Ferrara, Deborah; Pasetto, Laura; Bonetto, Valentina; Basso, Manuela (Frontiers in Neuroscience, 2018)
Amyotrophic Lateral Sclerosis (ALS) is the most common motor neuron disease in adulthood and primarily targets upper and lower motor neurons. The progression of the disease is mostly mediated by altered intercellular communication in the spinal cord between neurons and glial cells. One of the possible ways in which intercellular communication occurs is through extracellular vesicles (EVs) that are responsible for the horizontal transfer of proteins and RNAs to recipient cells. EVs are nanoparticles released by the plasma membrane and all evidence connecting ALS, intercellular miscommunication and EVs will be described in this review. We will mainly focus on mutant proteins causing ALS and their accumulation in EVs, along with the propensity of mutant proteins to misfold and propagate through EVs in a prion-like behavior. EVs are a promising source of biomarkers and state of the art in ALS will be discussed.